(NbA[NQ LASTO^KI (B((NwEDXMAK (B#6)s - Andrzej Sapkowski (Moscow (NiZDATELXSTWO asts, 2021)
(N~TO(B-(NTO KON^AETSQ(B. (NnADWIGAETSQ (BTedd Deireadh, (N~AS kONCA(B... (N|TO ^UWSTWUETSQ W WOZDUHE I W WODE(B, (NW [ELESTE TRAW I W GULE WETROW(B, (NW KROWI ZAKATOW I W OSLEPITELXNYH SPOLOHAH SEWERNOGO SIQNIQ NA ZUB^ATYH OSTRIQH WER[INY WELI^ESTWENNOJ ^ERNOJ BA[NI(B. (NmESTA(B, (NW KOTOROE WEDET NELEGKIJ PUTX PEPELXNOWOLOSU@ DEWO^KU NA WORONOJ KOBYLICE (B- (NPO ZALITOMU KROWX@ DRUZEJ POSTOQLOMU DWORU(B... (NPO ZALITOMU KROWX@ BOJCOW PESKU ARENY(B... (NPO ZALITOMU KROWX@ WRAGOW LXDU OZERA tARN mIRA(B. (NwEDX DELO NE W TOM(B, (N^TO TY TERPI[X STRADANIQ(B. (NdELO W TOM(B, (NKAK TY IH TERPI[X(B. (Ni WO IMQ ^EGO(B. (NlI[X POSTIG[IJ \TU ISTINU SMOVET WOJTI W (BTor Zireael. (NbA[N@ lASTO^KI(B.s
Keywords: Adventure; Fantasy; Fiction